Obstacles in the Implementation of Legal Protection for Auction Buyers Regarding the Employment of Auction Objects for The Execution of Mortgage Rights - Sulastri, Sulastri; Soegianto, Soegianto (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. Problems often arise in the auction winner's control of the auctioned object, which is the collateral, mortgage, or other collateral. One such problem is the debtor's or third party's reluctance to leave and vacate the auctioned object. This clearly does not provide legal certainty for the guaranteed protection of the auction winner's rights. This research was conducted using normative legal research (normative legal research method). Based on the research results, it can be seen thatThe current procedure for protecting the rights of auction winners has obstacles in the form ofGuarantees for the protection of rights for auction winners in the Regulation of the Minister of Finance of the Republic of Indonesia Number 122 of 2023 (PMK 122/2023) have not been specifically regulated. The auction can only be canceled by the request of the Seller or a provisional decision or decision from a general judicial institution, as regulated in the Regulation of the Minister of Finance (PMK) Number: 93/PMK.06/2010. Many debtors are reluctant to hand over the HT collateral object for auction, resulting in obstacles in the process of clearing the auction object after the auction. Intervention by third parties who feel disadvantaged by the auction can hinder the process.Keywords: Auction; Law; Mortgage; Protection.